Effect of off-axis angle on tension failures of laminated moso bamboo-poplar veneer composites: An in situ characterization. (15th December 2021) - Han, Shanyu; Chen, Fuming; Li, Haidong; Wang, Ge
Graphical abstract: Highlights: The biomaterial composite developed herein was inspired by the natural "hard-soft-hard" structure of the bamboo wall. In-situ characterization methods were utilized to observe the dynamic fracture behaviors of laminated bamboo-wood veneer composites under off-axis tensile loadings. The synergistic strengthening and toughening mechanism of moso bamboo-poplar veneer composite was determined to comprise both internal and externaltoughening. The maximum specific strength and specific modulus were 290.31 MPa·cm 3 ·g −1 and 23.84 GPa·cm 3 ·g −1, which are higher than other conventional biomaterials and even steel alloy. Abstract: Inspired by the natural gradient structure of the moso bamboo wall, a hybrid moso bamboo（B)Wood(W) veneer Composite (BWC) was developed with a specific structure of [B0° / W90° / B0° ]. The dynamic fracture behaviors and damage mechanism of the BWC were characterized using in situ scanning electron microscopy. X-ray micro- computed tomography imaging was employed to verify the off-axis tensile mechanical properties. The results showed that the maximum tensile strength and modulus of the BWC under off-axis loadings were 232.25 MPa and 17.47 GPa, respectively. Meanwhile, the maximum specific strength and specific modulus of the BWC were 290.31 MPa·cm 3 ·g −1 and 23.84 GPa·cm 3 ·g −1, respectively, which are higher than both natural wood (95.26 MPa·cm 3 ·g −1, 10.82 GPa·cm 3 ·g −1 ), bamboo (208.56 MPa·cm 3 ·g −1, 15.74 GPa·cm 3 ·g −1 ) and even steel alloy (237.86 MPa·cm 3 ·g −1, 21.98 GPa·cm 3 ·g −1 ). Compared to reorganized bamboo (RB), the porosity of the BWC was 61.1% lower. The BWC was strengthened via internal toughening mechanisms ( i.e. fiber bridging) and external toughening mechanisms ( i.e. multiregional distribution of micro-cracks). This work highlights methods to design high-performance bio composite from commonly used biomaterials through synergistic strengthening and toughening mechanisms, which has significant advantages in the ever-growing construction industry.